Uso de área e hábitos alimentares de Lontra longicaudis (Olfers, 1818) em uma área de caatinga do baixo rio São Francisco, Sergipe/Alagoas, Brasil - Terra, Rodrigo Farias de Carvalho (2016)
The Neotropical otter Lontra longicaudis (Olfers, 1818) have a large distribution, occurring in great part of Latin America, from northwestern of Mexico to northern of Argentina and in all Brazilian territory. The majority of works about L. longicaudis in Brazilian northeastern treats only on occurrence records. Upon the distribution in Caatinga, there is no information in literature concerning the species. The diet consists of fishes and crustacean. Therefore, L. longicaudis inhabits regions associates to fluvial systems. It is encountered more easily in areas where there is no intense anthropic activity. This way, the work had the objective identify what the ecological parameters that influence a population of L. longicaudis in a region of Caatinga: how the margin characteristics, with respect to substrate and to anthropic alteration level, can influence the frequency of use; characterize the feed habits and verify how the frequency of feed items varies throughout the year. The study has realized between January and November/2015 in a stretch of 10 km in Low São Francisco River, among the municipalities of Piranhas/AL, Poço Redondo e Canindé de São Francisco/SE, in Amortization Zone of Natural Monument Grota do Angico, a Caatinga area where were presents some riverine communities. The monthly frequency of use of the 83 latrines identified and categorized as substrate type and anthropic disturb level were compared with availability of margins in the same categories. Fourteen shelters were described as substrate, disturb, structure and origin. The major frequencies of use of latrines were in rocky outcroppings and islands. The sand beaches were significantly less used when under high disturbed level. The rocky beaches were avoided. Environment with human presence constant were significantly less used. Upon diet, the analysis of 184 fecal samples monthly collected showed the major presence of fishes followed by crustaceans. In addition, birds were identified. The main fish’s families were Anostomidae, Cichlidae, Loricariidae e Iguanodectidae; and de crustacean’s were Palaemonidae. Were less important the fish’s families Erythrinidae e Serrasalmidae; and crustacean’s Atyidae. There was no sazonal variation in the composition of L. longicaudis’ diet. However, Macrobrachium spp. was significantly more frequent in dry station, possibly due variation in prey availability.